STUDY OF GOVERNMENT AGENCY DELAYERING POLICY: URGENCY AND CHALLENGES - Marianto Marianto; Rido Rizky; Manan Apriliyanto (Taksasila Edukasi Insani, 2026)
This article examines the urgency and challenges of delayering policies in government agencies. Delayering, as a core component of bureaucratic reform, aims to create an organizational structure that is leaner, more adaptive, and performance-oriented. The research method employed is a systematic literature review, analyzing academic journals, government policy documents, and official articles. The findings indicate that the urgency of delayering lies in its potential to improve organizational agility, coordination effectiveness, and decision-making speed. Furthermore, it promotes individual accountability and simplifies coordination flows. However, structural changes must be synchronized with shifts in organizational culture, leadership patterns, and work value systems. This process demands transformational leadership capable of managing resistance and fostering a new organizational culture. The article recommends several policy implications: continuous development of functional competencies, integration with performance management systems, and strengthening change management. These insights serve as a practical reference for policymakers in optimizing the implementation of delayeringKeywords: Bureaucratic Reform, Change Management, Delayering, Organizational Simplification